Adenosine receptors are the on‐and‐off switch of astrocytic cannabinoid type 1 (CB1) receptor effect upon synaptic plasticity in the medial prefrontal cortex - Gonçalves-Ribeiro, Joana (2024)
© 2024 The Authors. GLIA published by Wiley Periodicals LLC. This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.